Marine Enzymes Sources, Biochemistry and Bioprocesses for Marine Biotechnology - Trincone, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents contributions from scientists who are directly involved in the potential of marine enzymes as useful tools in biocatalysis; the results of enzymatic bioprospecting in gross marine environments are acknowledged, including two review articles on general enzymatic processes and microalgal enzymes. In addition, studies on structural characterizations, biological functions and aspects related to the complexity of marine enzyme-based bioprocesses are discussed. Prominent conclusions by many scientists in the field of marine biotechnology emphasize that, due to marine biological diversity and the specificity of biological marine metabolisms, the study of biocatalysts on a global scale from this environment is just starting, and possesses huge potential for the development of applications with industrial benefits.